Efforts to Enhance the TVET Teachers Competencies through Apprenticeship Approach Pattern in Industry - Ratnata, I Wayan (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2015)
Facing ACFTA (ASEAN - China Free Trade Area) in 2015 (ASEAN 2012), nations in the region must be ready with variety of challenges that will occur. In this paper will be focusing how to prepare vocational teachers who will teach in vocational education in order to produce skilled graduates are ready for work and appropriate to the demands of the world of company or industry. Up to now, the existence of vocational teacher education in the region ASEAN-China (RCP:2012) need to be improved, primarily in teaching learning process and need to have enough experience in company or industry. Indonesia is one of the member of the ASEAN’s Countries still experiences difficulty to improve vocational teachers’ education in order to be ready to teach. The most difficult in preparing of vocational teacher education is in terms of their skill. This study was using case study method, in which data collected through interview in depth to students in Department of Electrical Engineering Education, Faculty of Vocational and Technology Education, Universitas Pendidikan Indonesia. According to the questionnaire done to vocational teachers, students who are doing teaching practice in vocational school, can be concluded that enhancing the quality of vocational teacher education cannot just be provided through theory and should also be provided chance students doing apprenticeship in the world of industry or workplace. In this regard, seemingly it is necessary to have a breakthrough for increasing the students competencies in order fresh graduates are ready for work.